2014
DOI: 10.3906/sag-1308-65
|View full text |Cite
|
Sign up to set email alerts
|

Association analyses of oxidative stress, aerobic capacity, daily physical activity, and body composition parameters in patients with mild to moderate COPD

Abstract: IntroductionChronic obstructive pulmonary disease (COPD), one of the most common chronic diseases, is a major cause of morbidity. Oxidative stress is a situation of imbalance between free radicals and antioxidants in favor of the oxidants (1). Today, habitual smoking is the most significant threat to the world's population (2). The development of COPD is mainly associated with tobacco or biomass smoke-induced oxidative stress. Smokers are exposed to thousands of reactive chemicals and trillions of radicals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The data were analyzed using the manufacturer's software, and body fat percentage and lean body mass were determined for each patient . Waist and hip circumference measurements were taken at anatomical positions with a 7 mm wide tape measure . The waist/hip ratio was also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The data were analyzed using the manufacturer's software, and body fat percentage and lean body mass were determined for each patient . Waist and hip circumference measurements were taken at anatomical positions with a 7 mm wide tape measure . The waist/hip ratio was also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Fat deposits between muscles and other body structures may mechanically affect diaphragm expansion, and may also decrease lung and chest wall compliance. culminating with a decrease in lung volume and overload on inspiratory muscles (Genc, et al, 2014;Melo, de Melo, de Menezes Filho, & Santos, 2011;Paulo, et al, 2015;Ribeiro, Araújo, SouzaMachado, & Ribeiro, 2007;Thakker, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, it is considered a functional test that allows from standard protocol to measure pulmonary volumes, capacities and flows, thus evaluating the existence or not of respiratory pathologies of restraining, obstructive or mixed order (Costa, 2011;Jagia & Hegde, 2014;Pereira et al, 2002;Teixeira, et al, 2012;Trindade, de Sousa, & Albuquerque, 2015) Clinical evaluation studies on lung function have shown that people with a regular physical activity level get better results in pulmonary function tests when compared to sedentary people (Durmic et al, 2015;Humphreys, McLeod, & Ruseski, 2014;Paulo et al, 2015). Moreover, regarding nutritional status, individuals with extreme nutritional imbalance -with body mass index (BMI) indicating low weight and obesity, tend to be more prone to develop respiratory diseases when compared to those with normal BMI (Genc et al, 2014;Humphreys, et al, 2014;Liu, Roberts, Moyer-Mileur, & Samson-Fang, 2005;Paulo, et al, 2015;Thakker, 2014). Studies show that when affected by a respiratory disease the individuals need to include exercise in their routines and keep their BMI within the normal range due to its positive impact on maintenance, treatment and prevention of comorbidities (Demeyer et al, 2014;Fenger et al, 2014;Pakhale, Baron, Dent, Vandemheen, & Aaron, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The participants were instructed to avoid eating or drinking within 4 h, using diuretics within 7 days, participating in strenuous exercise for 24 h, and consuming alcohol for 48 h before the test procedure. The data were analyzed using the manufacturer's software, and body fat percentage, total body fat, and lean body mass were determined for each patient [17].…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…The basic premise of the bioelectrical impedance analysis procedure is that the volume of fat-free tissue in the body is proportional to the electrical conductivity of the body [16]. Some precautions were taken before the measurements [16,17]. The participants were instructed to avoid eating or drinking within 4 h, using diuretics within 7 days, participating in strenuous exercise for 24 h, and consuming alcohol for 48 h before the test procedure.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%